Understanding the Implementation of Good Government Governance (GGG) on The Quality of Public Services - Febrilda Putri Budiawan; Tutty Nuryati (Journal of Accounting and Finance Management, 2022)
Good Government Governance (GGG) is good governance in a business that is based on professional ethics in business and work as well as improving better regulations for a government agency. There are three things that are played in good government governance (GGG), namely public transparency, public accountability, and community participation. This study aims to examine whether public transparency, public accountability, and public participation on the quality of public services in an empirical study of local taxpayers in Bekasi City. The research method used is a quantitative method. Primary data obtained through the results of a questionnaire with a sample of 96 respondents. The object of this research is individual taxpayers and restaurant taxpayers. The data collection in this study used purposive sampling technique and the measurement scale used a Likert scale 1-5. Data analysis using Partial Least Square (PLS) Smart PLS 3.3.9 program. The results of the study show that 1) Public Transparency has a positive and significant effect on the quality of public services; 2) Public Accountability has a positive effect on the quality of public services; 3) Community participation has a positive and significant effect on the quality of public services.